A comparative analysis on the research competency of medical students across the COVID-19 periods - Euihyeon Na; Sang Ah Lee; Jung-Sik S. Huh; Kyu Bum Seo; Eun Kwang Choi; Sang-Pil P. Yoon (Scientific Reports)
Abstract The ability to conduct research and utilize its findings has been a fundamental competency for medical students, often assessed through the observable research outcomes. This study aims to compare the research competency of medical students before, during, and after the COVID-19 pandemic to explore the future direction of research education in medical schools. We collected information on research outcomes submitted by medical students as graduation requirements during the pre-COVID-19, pandemic, and post-COVID-19 periods based on the duration of social distancing. The research outcomes were classified into two categories: publication of a paper and presentation at a conference. We compared variables such as authorship, type of journal or conference, and type of literature or presentation. The research outcomes submitted by all medical school graduates at their senior year from 2018 to 2023 were included in the analysis. The graduation requirements were usually achieved by publishing a paper (67.5%) with a faculty of clinical medicine (63.5%) in the fourth year (50.0%), regardless of COVID-19 pandemic. The findings highlighted the significant impact of the COVID-19 pandemic on the research outcomes of medical students. Post hoc analysis revealed that while the quality of published papers improved during the COVID-19 pandemic, there was a regression in author contributions in the post-pandemic period. The impact of the COVID-19 pandemic on medical students’ experiences with research is likely that the weakened student initiative observed in participating in and conducting research will persist, especially after the pandemic. Therefore, it is imperative to implement strategies to increase motivation and empower medical students to research.